An ApoA-I Mimic Peptide of 4F Promotes SDF-1α Expression in Endothelial Cells Through PI3K/Akt/ERK/HIF-1α Signaling Pathway - Lv, Kaixuan; Kong, Lingyu; Yang, Mei; Zhang, Linlin; Chu, Shangmin; Zhang, Lichun; Yu, Jielun; Zhong, Guoshen; Shi, Yanhua; Wang, Xia; Yang, Nana (Frontiers in Pharmacology, 2022)
Atherosclerosis (AS) seriously impairs the health of human beings and is manifested initially as endothelial cells (ECs) impairment and dysfunction in vascular intima, which can be alleviated through mobilization of endothelial progenitor cells (EPCs) induced by stromal-cell-derived factor-1α (SDF-1α). A strong inverse correlation between HDL and AS has been proposed. The aim of the present work is to investigate whether 4F, an apolipoprotein A-I (apoA-I, major component protein of HDL) mimic peptide, can upregulate SDF-1α in mice and human umbilical vein endothelial cells (HUVECs) and the underlying mechanism. The protein levels of SDF-1α were measured by ELISA assay. Protein levels of HIF-1α, phosphorylated Akt (p-Akt), and phosphorylated ERK (p-ERK) were evaluated by Western blotting analysis. The results show that L-4F significantly upregulates protein levels of HIF-1α, Akt, and ERK, which can be inhibited by the PI3K inhibitor, LY294002, or ERK inhibitor, PD98059, respectively. Particularly, LY294002 can downregulate the levels of p-ERK, while PD98059 cannot suppress that of p-Akt. D-4F can upregulate the levels of HIF, p-Akt, and p-ERK in the abdominal aorta and inferior vena cava from mice. These results suggest that 4F promotes SDF-1α expression in ECs through PI3K/Akt/ERK/HIF-1α signaling pathway.